2018
DOI: 10.21134/haaj.v18i2.390
|View full text |Cite
|
Sign up to set email alerts
|

Imagen corporal, búsqueda de sensaciones sexuales y prácticas sexuales más seguras en hombres que tienen sexo con hombres de Nuevo León, México

Abstract:  Los hombres que tienen sexo con hombres (HSH) representan un grupo clave de mayor afectación en la transmisión del virus de inmunodeficiencia humana, la principal forma de prevención es mediante la conducta sexual segura, sin embargo existen factores que pueden incidir negativamente como puede ser la imagen corporal y la búsqueda de sensaciones sexuales. Objetivo. Determinar la influencia de la imagen corporal y la búsqueda de sensaciones sexuales en la conducta sexual segura en HSH. Metodología. Se r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…They are interested in activities that provoke intense experiences, such as not using a condom or giving more importance to physical attraction than to knowing the partner [43,56]. The heightened sensation-seeking is also expressed through greater drug use, although this relationship does not always directly influence on risky sexual behavior [25,57]. High rates of drug use can be attributed to considering some drugs as a normative part of certain sexual dynamics [58].…”
Section: Explanatory Variables For Sexual Risk Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…They are interested in activities that provoke intense experiences, such as not using a condom or giving more importance to physical attraction than to knowing the partner [43,56]. The heightened sensation-seeking is also expressed through greater drug use, although this relationship does not always directly influence on risky sexual behavior [25,57]. High rates of drug use can be attributed to considering some drugs as a normative part of certain sexual dynamics [58].…”
Section: Explanatory Variables For Sexual Risk Behaviormentioning
confidence: 99%
“…In the case of the behavioral variables, sexual compulsion and sensationseeking are two of the most powerful predictors of sexual risk behavior in MSM [22]. These variables are associated with the presence of negative attitudes toward condom use, reduced use of condoms during anal intercourse, a larger number of casual partners, and a greater likelihood of engaging in group sex [23,24,25,26]. In addition, a recent study by the European Center for Disease Prevention and Control confirms that the use of some drugs is part of the sexual dynamic of many men [1].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Zuckerman's Sensation Seeking Theory [21] posits a clear relationship between this trait and impulsivity, describing the disinhibition factor as an impulsive way of seeking sexual stimulation [17]. Some studies on the matter have revealed that people with more impulsive traits and with a greater tendency to seek sensations are those that behave in a sexually riskier manner [22,23]. This suggests that people with higher scores in sensation seeking are those that find it more difficult to inhibit certain behaviors they find arousing.…”
Section: Erotic Desire and Personality Factorsmentioning
confidence: 99%